Avaliações neuroquímicas, enzimáticas e comportamentais em ratos infectados experimentalmente com trypanosoma evansi e utilização da curcumina como possível agente terapêutico - Wolkmer, Patricia (2013)
The pathogenesis of Trypanosoma evansi (T. evansi) infection on central and peripheral nervous system (CNS) and immunologic system it is not completely understood. This study was conducted to investigate the effects of infection by T. evansi on the behavioral performance of rats, relating them to neurochemical alterations of the glutamatergic system and activity of important enzymes such as Ca2 + ATPase, Na + / K + ATPase and acetylcholinesterase (AChE) in the brain. Furthermore, we evaluated the activity of AChE in the T. evansi, using a biochemical protocol and discussed some possibilities for the interaction between the presence of this enzyme in the parasite and its possible relation with the host. Also, we investigated the in vivo effect of curcumin as an antitrypanosomal agent to contribute in the search for new therapies. To this end, we conducted a series of studies, as follow that are presented as scientific articles: in the Article I are presented data from rats experimentally infected with T. evansi and in which the activity of AChE in total brain, cerebellum and blood and plasma butyrylcholinesterase activity on days 3 (T3) and 5 (T5) post infection (pi) were evaluated. In the Article II trypanosomes were isolated by Dietil Amino Etil-celulose column to perform enzymatic assays of AChE activity in the parasite. Article III presents the results of daily oral administration of Curcumin (20 or 60 mg / kg) as a preventive treatment (for 30 or 15 days pre-infection) or as curative treatment (for 15 days pi) for T. evansi infection in rats. The animals were evaluated for parasitemia, proinflammatory cytokines (IFN-γ, TNF-α, IL-1, IL-6) and anti-inflammatory (IL-10) in plasma. Also blood AChE activity was studied. In the manuscript I were evaluated behavioral changes (memory and anxiety), glutamate uptake, activity of AChE and ATPases (Ca +2 and Na +, K +) in brain structures of T. evansi infected rats (5 and 30 dpi). Together these studies suggest that rats infected with T. evansi have cognitive impairment, probably caused by changes on energy metabolism (ATPases) and in the cholinergic and glutamatergic systems. That way, alterations observed during behavioral tests probably indicate the progression of clinical disease as a result of neurochemical dysfunction. It was also demonstrated that it is possible to biochemically detect the AChE activity in the T. evansi and this could cause the hydrolysis of acetylcholine in the parasite. It was also demonstrated that pretreatment with curcumin induces immunomodulatory effects, altering inflammatory cytokines and activity of AChE in rats infected with T. evansi. The treatments reduced parasitic load and mortality. Therefore, curcumin should be considered as a feeding supplement in trypanosomiasis endemic areas.